Selected aspects of nursing care for a patient after ischemic stroke in a care and treatment facility - a case study - Pawłowska-Muc, Agnieszka; Borek, Monika; Maciąg, Dorota; Cichońska, Małgorzata; Oborska, Sylwia; Deja-Makara, Beata (Journal of Education, Health and Sport, 2024)
Cerebrovascular diseases (including strokes) are currently the second leading cause of death in the world [1,2]. In Poland, statistical data are quite diverse, depending on their source. Stroke patients are often at risk of chronic disability. A significant number of them are doomed to lose their independence and self-care for the rest of their lives. The aim of the study is to present selected nursing problems and ways to solve them in a patient after ischemic stroke who requires round-the-clock care in the field of nursing and care services as part of inpatient long-term care. The subject of the study is the process of nursing a patient diagnosed with ischemic stroke who requires round-the-clock care in the field of nursing and care services as part of long-term care. The study uses a research method - a case study, supported by individual observation, measurements, interview and analysis of medical records. Two scales were used to assess the patient's condition: Barthel and Norton. Conclusions: The individual care plan takes into account the most important problems arising from the specificity of the disease entity, needs and individual situation of the patient. The patient's care problems after a stroke are presented and proposed an effective solution to ensure the best possible care. Nursing and care difficulties have been properly recognized, which has enabled appropriate nursing interventions. Due to systematic prophylactic measures, the patient did not suffer from complications. A detailed interview and careful observation made it possible to plan and implementation of interventions (not only nursing) to provide comprehensive care. The urgent procedure of admitting the patient to the care and treatment facility contributed to the improvement of the quality and availability of health care services, which translated into an improvement in the patient's general condition.